A methodology to measure residual stresses close to the yield stress using an optical hole drilling method - Wilvert, Thiago (2025)
Tese (doutorado) - Universidade Federal de Santa Catarina, Centro Tecnológico, Programa de Pós-Graduação em Engenharia Mecânica, Florianópolis, 2025.